NON-ALCOHOLIC FATTY LIVER DISEASE AND CARDIOVASCULAR RISK: SCIENTIFIC PROBLEM STATE - O. M. Drapkina; A. A. Yafarova (Столичная издательская компания, 2017)
Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide, which is frequently present in patients with atherosclerosis or its complications (myocardial infarction, stroke). Subsequently it was revealed that NAFLD may increase cardiovascular risk independently of traditional cardiovascular risk factors. Possible mechanisms of NAFLD-induced increasing cardiovascular risk are increased oxidative stress, subclinical inflammation, insulin resistance, endothelial dysfunction and deranged аdipocytokines profile. Such risk factors as arterial hypertension, dyslipidemia, obesity, diabetes mellitus type 2 often coexist with NAFLD and contribute to increased cardiovascular risk in these patients. Thus, NAFLD can be considered as an additional risk factor of cardiovascular diseases. In this article we discuss in detail the NAFLD-induced mechanisms which increase the cardiovascular risk regardless of traditional risk factors.